Primary Retroperitoneal Malignant Melanoma with Involvement of Iliac Artery and Vein - Aislyn Oulee; Ling Xu; Scott Worswick (Case Reports in Medicine)
Primary retroperitoneal melanoma is a very rare extracutaneous presentation of melanoma. In this case report, we present a 65-year-old female with unilateral lower extremity edema secondary to occlusion of iliac vessels by a primary retroperitoneal melanoma tumor. We also review the findings in other cases previously described in the literature.